P830 Feasibility of an online HPV self-collection screening program in canada: digital health literacy in south asian women. (14th July 2019) - Zhang, Sandy; Pedersen, Heather; Smith, Laurie; Sarai Racey, C; Niekerk, Dirk Van; Lee, Marette; Gilbert, Mark; Haag, Devon; Ogilvie, Gina
Abstract : Background: Women who do not regularly attend cervical cancer screening are at increased risk for cervical cancer. In British Columbia (BC), approximately 30% of women aged 21–69 years are under-screened. As cervical cancer screening in BC moves towards the use of primary HPV testing, there is an opportunity to address screening barriers women face through self-collected, rather than clinician collected specimens. CervixCheck is an internet-based program for HPV self-collection being piloted in communities across BC with low screening rates. To inform the implementation of CervixCheck, we investigated digital health literacy (DHL) in South Asian women. Methods: A cross-sectional anonymous survey was administered July-August 2018 through collaborating primary care clinics in predominantly South Asian communities in the Fraser Health Region of BC. The study population was a convenience sample of women 30–65 years of age, presenting at a primary care clinic. Women were administered the survey on a tablet, which collected demographic, screening history, and internet use information. DHL was measured using the validated eHEALS and Digital Health Literacy Instruments. Results: 51 women participated from four family practices where 30% of women were 50 years or older. 29.4% of women self-reported not having had a Pap test in the last 3 years. English (86%) and Punjabi (58%) were the most common languages participants reported reading and speaking. Majority of women reported using the internet daily (82.4%), with mobile phones being the most common device (72.6%). DHL was higher in under-screened women. Over 80% of women responded that they would be likely to very likely to participate in self-collected screening using CervixCheck. Conclusion: The survey revealed CervixCheck is a promising digital health platform to increase cervical cancer screening uptake among under-screened South Asian women. Findings were used to inform CervixCheck website design and program resources in preparation for its launch. Disclosure: No significant relationships.